PENGARUH TEKNIK AUDIT BERBANTUAN KOMPUTER, KOMPETENSI AUDITOR, DAN KECERDASAN SPIRITUAL PADA KUALITAS AUDIT BPK BALI - Januraga, I Ketut; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
The results of such audit examination by the BPK audit findings demonstrate the ability of auditors to detect errors contained in the financial statements that shows the good quality of the audit. This study aims to determine the effect TABK, auditor competence, Spiritual Intelligence on Audit Quality. The sampling method used in this study sample is saturated. Data were collected using a questionnaire survey method. Respondent data that can be processed is 43 respondents. Testing the validity and reliability of the instrument variables used in this study have high levels of validity and reliability that can be accepted. Data analysis technique used is multiple linear regression analysis. Results of multiple linear regression analysis by observing the Adjusted R2 value, indicating that the variable quality of the audit can be explained by the variable TABK, auditor competence, Spiritual Intelligence at 48.80%. Hypothesis testing with statistical t test showed that the variables TABK, auditor competence, intelligence Spiritul significant positive effect on audit quality.
Keywords: Computer Assisted Audit Techniques; Competence Auditor; Spiritual Intelligence; Quality Audit